Catalysts of Customer Satisfaction: A Quantitative Analysis of Brand Image, Service Quality, and Store Atmosphere: Faktor-Faktor Penentu Kepuasan Pelanggan: Analisis Kuantitatif Brand Image, Kualitas Layanan, dan Atmosfer Toko - Firman Ardiansyah; Lilik Indrayani (Academia Open, 2024)
This research aims to investigate the impact of Brand Image, Service Quality, and Store Atmosphere on Customer Satisfaction in the context of Starbucks Coffee consumers at Suncity Mall Sidoarjo. Utilizing a quantitative approach, data was collected from 100 respondents through questionnaires. The analysis employed multiple linear regression with SPSS 18.0, revealing that Brand Image, Service Quality, and Store Atmosphere significantly influence Customer Satisfaction. These findings have important implications for businesses seeking to enhance customer satisfaction and loyalty through strategic management of these factors. Highlights: Influence of Key Factors: Investigates how Brand Image, Service Quality, and Store Atmosphere impact Customer Satisfaction. Quantitative Approach: Employs a quantitative methodology with 100 respondents to analyze the relationships. Practical Implications: Offers insights for businesses to enhance customer satisfaction and loyalty through strategic management. Keywords: Brand Image, Service Quality, Store Atmosphere, Customer Satisfaction, Quantitative Study